2021
DOI: 10.2147/rmhp.s299180
|View full text |Cite
|
Sign up to set email alerts
|

Does Hearing Impairment Affect Mental Health Among Chinese Older Adults? Evidence from the Chinese Longitudinal Healthy Longevity Survey

Abstract: Background and Aim Hearing impairment is a commonly reported chronic condition among older adults. Hearing impairment is significantly associated with reduced quality of life and diminished function status. This study aimed to investigate the association between hearing impairment and mental health among Chinese older adults, with a focus on exploring the moderating effects of social participation and exercise on this association. Methods The data of this study were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In addition, disability may contribute to cognitive impairment as well as depressive symptoms in a reciprocal manner. Depressive symptoms affect patients’ ability to engage in cognitively stimulating activities, as well as their participation in the workforce and mental challenges ( 55 ). Meanwhile, people with depressive symptoms tend to have fewer social networks than healthy controls, and they are more likely to experience negative interactions and social strain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, disability may contribute to cognitive impairment as well as depressive symptoms in a reciprocal manner. Depressive symptoms affect patients’ ability to engage in cognitively stimulating activities, as well as their participation in the workforce and mental challenges ( 55 ). Meanwhile, people with depressive symptoms tend to have fewer social networks than healthy controls, and they are more likely to experience negative interactions and social strain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are no evidence indicating that, social participation or exercise relieved the adverse effect of hearing impairment on depression status. 3 Shoham, N., Lewis, G., Favarato, G., & Cooper, C. ( 2019), conducted a study on prevalence of anxiety disorder with hearing impairments, and found that, prevalence of anxiety is higher among people with hearing impairment than the general population; our findings indicate that this excess morbidity may be related to the hearing impairment itself, as it was associated with the severity of impairment, and reduced after surgical treatment. Clinicians should be aware of the potential impact of hearing on mental health, and that where hearing ability can be improved, this may reduce anxiety.…”
Section: Discussionmentioning
confidence: 53%
“…Similar to sarcopenia, SO has been linked to frailty and osteoporosis (Fan et al, 2021 ; Chou et al, 2022 ). Moreover, individuals with SO are at greater risk of metabolic disorders and reduced physical performance, such as walking speed, than those with sarcopenia or obesity alone (Sun et al, 2021 ; Tan et al, 2022 ). It was proposed that individuals with SO tended to suffer from impairment of living functions and lower physical capabilities during aging (Hayes and Preacher, 2014 ; Jia et al, 2020 ; Tanaka et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%